PYELOPLASTİ OPERASYONLARIMIZIN DEĞERLENDİRİLMESİ - KAYA, Esat; KAPLAN, Mustafa; ALAGÖL, Bülent; İNCİ, Osman and ATAKAN, İrfan Hüseyin (Cerrahpaşa Medical Journal, 2014)
Background and Design.- Totally 36 patients who had undergone pyeloplasty operation for ureteropelvic obstruction in our clinic between 1986 and 1998 were evaluated retrospectively. Results.- The mean age of these cases was 30,7 years, of which 12 were female and 24 male. Anderson Hynes technique had been undertaken in 30 patients, Foley Y-V plasty in 5, Culp DeWeered spiral flap in 1 patient. In all cases other than those who had undergone Foley Y-V plasty required nephrostomy and stend application. The development of severe wound infection requiring reoperation in 1 patient and a late fistula healing spontaneously in an other was observed. The mean duration of hospital stay was 9 days. Conclusion.- In all cases an improvement had been noted when the findings of preoperative urography were compared with those taken 3 months after the operation.